Prognostic value of nutritional and inflammatory indicators in females with esophageal squamous cell cancer: A propensity score matching study - Li, Yuping; Luo, Huaichao; Ye, Bo; Zhang, Kaijiong; Liu, Chang; Zu, Ruiling; Ni, Sujiao; He, Qiao; Rao, Lubei; Wang, Qifeng; Wang, Dongsheng (Frontiers in Genetics, 2022)
Background: Esophageal squamous cell cancer (ESCC) is a disease with a male predominance. Accordingly, the applicability of prognostic indicators values previously set for the general population with ESCC has not been reported for determining the physical state in female. Methods: A total of 2660 patients with ESCC were pooled in this study. We determined the differences of the nutritional and inflammatory indicators between gender by sex-stratified survival analysis in all cohort (n=2660) and matching cohort (n=483 pairs) separately. Propensity score matching (PSM) was employed to eliminate selection bias between gender. We further performed the prognostic value of total cholesterol (TC) by subgroup analysis in the female cohort. Results: There were a total of 2,660 patients with ESCC, of whom 2173(81.7%) were male and 487(18.3%) were female. For cohort with or without matching, the results showed the prognostic nutritional index and systemic immune inflammation index were related to prognosis in male but not in female. Contrarily, TC was a significant prognostic factor of female not for male. Furthermore, TC was an independent prognostic factor in female with ESCC. Female patients with high TC level had significant poor OS in stages III and IV. And with or without postoperative adjuvant treatment. OS was significantly poorer in female patients with high TC level. Conclusion: Based on a much larger cohort, we confirmed that gender was a significant prognostic factor of ESCC patients. Interestingly, we found a significant difference in TC related to ESCC prognosis between gender. Collectively, TC might be an independent prognostic factor in the female with ESCC.